Acute Bilateral Ophthalmoparesis with Pupilary Areflexical Mydriasis in Miller-Fisher Syndrome Treated with Intravenous Immunoglobulin - Theocharis Papanikolaou; Cath Gray; Bernard Boothman; Gerald Naylor; George Mariatos (Journal of Ophthalmology)
Miller-Fisher syndrome (MFS) is a rare condition characterized by the classical triad of ophthalmoplegia, ataxia, and areflexia (Fisher, 1956). It is considered a variant of Guillain-Barré syndrome (GBS) with which it may overlap, or it can occur in more limited forms. We report a case of a thirty-five-year-old male who presented with a six-day history of diplopia, following a recent chest infection. On examination, he was found to have bilateral sixth nerve palsy, bilateral fourth nerve palsy, bilateral areflexical mydriasis, ataxia and total absence of reflexes. After excluding other conditions, a diagnosis of Miller-Fisher syndrome was made. The patient was administered intravenous immunoglobulin and made an uneventful recovery.